2016
DOI: 10.1038/srep37644
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 6/8/11-Amino/Chloro-Oxoisoaporphine and Group-10 Metal Complexes and Evaluation of Their in Vitro and in Vivo Antitumor Activity

Abstract: A series of group-10 metal complexes 1–14 of oxoisoaporphine derivatives were designed and synthesized. 1–14 were more selectively cytotoxic to Hep-G2 cells comparing with normal liver cells. In vitro cytotoxicity results showed that complexes 1–6, 7, 8, 10 and 11, especially 3, were telomerase inhibitors targeting c-myc, telomeric, and bcl-2 G4s and triggered cell senescence and apoptosis; they also caused telomere/DNA damage and S phase arrest. In addition, 1–6 also caused mitochondrial dysfunction. Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…The ESI † provides the detailed procedures of other experimental methods, including the measurement of mitochondrial membrane potential (by JC-1 staining), ROS generation, intracellular free Ca 2+ , Western blot, and caspase-3/9 activity. The procedures were similar to those given in the previous work of Chen et al 40…”
Section: Other Experimental Methodsmentioning
confidence: 90%
“…The ESI † provides the detailed procedures of other experimental methods, including the measurement of mitochondrial membrane potential (by JC-1 staining), ROS generation, intracellular free Ca 2+ , Western blot, and caspase-3/9 activity. The procedures were similar to those given in the previous work of Chen et al 40…”
Section: Other Experimental Methodsmentioning
confidence: 90%
“…An extensive study on complexes of Group 10 metals with oxoisoaporphine ligands (6‐amino‐, 8‐amino‐, 8‐chloro‐, and 10‐chloro‐11‐aminooxoisoaporphine; Figure ) has been performed . The findings demonstrated that 34 – 47 exhibited remarkably increased in vitro cytotoxicity and tumor growth inhibition against a panel of tumor cell lines, such as Hep‐G2, NCI‐H460, SK‐OV‐3, HCT‐8, and BEL‐7402, compared with those of the ligands alone.…”
Section: Structure Modificationmentioning
confidence: 99%
“…Treating the T‐24 cells with 0.5 μ m complex 1 and 18.0 μ m cisplatin for 24 h led to notable accumulation of cellular cobalt ((20.96 ± 1.06) ng Co/10 6 cells) and platinum ((12.03 ± 0.86) ng Pt/10 6 cells) compared with the control ( Figure ), respectively, suggesting that the uptake of the Co(III) complex 1 in T‐24 cells was higher than that of cisplatin. [ ][ ]…”
Section: Resultsmentioning
confidence: 99%
“…After the T‐24 cells were exposed to the Co(III) complex 1 (0.5 μ m ) for 24 h, the cobalt distributions in the nuclear fraction and the mitochondria fractions of the T‐24 cells were examined according to the reported method. [ ][ ] Figure shows that the cobalt accumulation was high in all fractions, especially in the mitochondrial fraction, probably because 1 activated the apoptotic pathways of the cells. However, cisplatin (18.0 μ m ) appears predominantly localized in the mitochondrial membrane fraction, with lesser accumulation in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation